Leuprorelin acetate hormone therapy in the management of ovarian endometriosis: A case report - Amirudin Amirudin; Sanoko Tjandra (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Endometriosis is a condition characterized by the growth of endometrial tissue outside the uterus, which can cause pelvic pain and problems in the reproductive system. Endometriosis usually occurs during reproductive age. The symptoms of endometriosis depend on the location of the endometrial cells. The main complaint that often appears is pelvic pain, so about 71-87% of cases are diagnosed due to severe chronic pain during menstruation, while only 38% are detected due to infertility problems. Proper treatment of endometriosis is necessary, as many women are often diagnosed too late, leading to suffering and decreased quality of life. One of the medical approaches used is hormone therapy. Purpose: To aprove Leuprorelin acetate hormone therapy in helping the treatment of Ovarian Endometriosis. Method: This descriptive analytic research used a case study approach involving a 37-year-old female patient with ovarian endometriosis at the Obstetrics and Gynecology Polyclinic of Dompu General Hospital. The study followed ethical principles and obtained informed consent. Data were collected through interviews, observation, physical examinations, medical records, and diagnostic documentation, using a head-to-toe assessment format. Data analysis was conducted concurrently with data collection, comparing findings with existing theories to support discussion and intervention recommendations. The analysis was narrative and observational, aiming to interpret the patient’s condition in relation to theoretical knowledge. Results: Hormone therapy with Leuprorelin acetate was administered in this case at a dose of 3.75 mg per injection for three months. The results of the ultrasound examination showed a reduction in the size of the ovarian mass, and the patient's pain significantly decreased. Conclusion: Leuprorelin acetate hormone therapy can serve as an effective alternative to surgery in managing symptoms of ovarian endometriosis.